Studying Of Image Intensity Distribution Of Elliptical Object (Elliptical Spread Function) - Al-Jizany, A. B. Hasan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work, a new formula of intensity distribution in image plane of elliptical object was founded (Elliptical spread function), by using optical system including circular aperture. The Gauss quadrature method of numerical integral was used for calculating equation’s integrals. Curves are shown for system having focal error and intensity distribution in focal axis.